Managing U.S. Atlantic large whale entanglements: Four guiding principles. (October 2017) - Borggaard, Diane L.; Gouveia, David M.; Colligan, Mary A.; Merrick, Richard; Swails, Kathryn S.; Asaro, Michael J.; Kenney, John; Salvador, Glenn; Higgins, John
Abstract: Fatal entanglements in fishing gear threaten marine mammal populations worldwide. The management of entanglements of large whales, such as the North Atlantic right whale ( Eubalaena glacialis ), with commercial fisheries, is a challenge given the species' small population size, economic consequences of regulations, and the general lack of data on entanglements. The U.S. Marine Mammal Protection Act (MMPA) requires development of programs to limit marine mammal entanglement in commercial fishing gear. Following a retrospective look at implementing aspects of the MMPA, a set of guiding principles were developed with associated best practices useful in reducing fatal large whale entanglement in fishing gear. Among these are: 1) involve stakeholders early in the decision making process; 2) establish a transparent management strategy that includes critical needs to guide research; 3) use a variety of tools such as an established process for receiving new information and ideas; and 4) incorporate adaptive management which considers the constraints of dynamic (rapid) changes to some fixed fishing gear. Efforts to reduce worldwide marine mammal bycatch will typically occur in a data-limited environment as experienced with U.S. Atlantic large whale entanglements. The guiding principles will remain as key tools for reducing large whale bycatch in fisheries as they build upon common practices. These insights developed over two decades of management can potentially help others to address similar bycatch problems. Highlights: Guiding principles and best practices useful in reducing bycatch are proposed. It is essential to involve stakeholders early in the decision making process. A transparent management strategy is important which includes any research needs. Apply a variety of tools such as an established process for receiving information. Use adaptive management and consider limits of rapid changes to some fishing gear.